2009
DOI: 10.1038/hdy.2009.9
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics and sites of illegitimate recombination revealed in the interspersion and sequence junctions of two nonhomologous satellite DNAs in cactophilic Drosophila species

Abstract: Satellite DNA (satDNA) is a major component of genomes but relatively little is known about the fine-scale organization of unrelated satDNAs residing at the same chromosome location, and the sequence structure and dynamics of satDNA junctions. We studied the organization and sequence junctions of two nonhomologous satDNAs, pBuM and DBC-150, in three species from the neotropical Drosophila buzzatii cluster (repleta group). In situ hybridization to microchromosomes, interphase nuclei and extended DNA fibers show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 47 publications
(73 reference statements)
4
27
0
Order By: Relevance
“…In another study, Casals et al [2005Casals et al [ , 2006 showed a preferential accumulation of several class-II transposable elements in pericentromeric zones of polytene chromosomes, defined as transitions between heterochromatin and euchromatin (probably ␤ -heterochromatin). Finally, using PCR, we did not find evidence of interspersion between one of the class II TE elements ( Galileo ) analysed by Casals et al [2005Casals et al [ , 2006, and satDNA repeats [Kuhn et al, 2009]. Thus, the available information suggests non-overlapping patterns or low levels of interspersion between the verified TEs and satDNAs in the buzzatii cluster.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In another study, Casals et al [2005Casals et al [ , 2006 showed a preferential accumulation of several class-II transposable elements in pericentromeric zones of polytene chromosomes, defined as transitions between heterochromatin and euchromatin (probably ␤ -heterochromatin). Finally, using PCR, we did not find evidence of interspersion between one of the class II TE elements ( Galileo ) analysed by Casals et al [2005Casals et al [ , 2006, and satDNA repeats [Kuhn et al, 2009]. Thus, the available information suggests non-overlapping patterns or low levels of interspersion between the verified TEs and satDNAs in the buzzatii cluster.…”
Section: Discussionmentioning
confidence: 87%
“…The microchromosomes (also known as 'dot' chromosomes) are also highly heterochromatic. In previous studies, we determined the chromosome location of 2 satDNA families, pBuM and DBC-150, on the metaphase chromosomes of several species of the buzzatii cluster [Kuhn et al, 2007[Kuhn et al, , 2008[Kuhn et al, , 2009. In D. serido , fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of these sequences to change their copy number is thought to promote chromosomal rearrangements (Badaeva et al, 2007). For example, satellite DNA families are involved in recombination events in Drosophila (Kuhn et al, 2009) and play a central role in chromosome evolution in plants (Raskina et al, 2008). The role of several SSRs in chromosome organization has also been demonstrated in wheat and rye (Cuadrado and Schwarzacher, 1998).…”
Section: Chromosomal Rearrangementsmentioning
confidence: 99%
“…Alternatively, the three DBC-150 variants of D. martensis may be part of a higher-order repeat, i.e., multimers with a number of diverged monomers. For example, in one species of the BCS, D. antonietae, we found DBC-150 repeat units made up of dimers (2-mer) displaying 12.2% variability between the two subrepeats, but 6% between the dimers (Kuhn et al 2009). Unfortunately, we could not examine the genomic and/or chromosomal organization of DBC-150 variants in D. martensis because living strains are no longer available in Drosophila stock centers.…”
Section: Discussionmentioning
confidence: 99%
“…The DBC-150 repeats from D. martensis were clearly allocated in a specific branch, separated from all other DBC-150 variants found in the BCS, including the more differentiated higher-order repeats of D. serido and the DBC-150 repeats from some sequence junctions found in D. gouveai and D. antonietae (Kuhn et al 2009). The 11 DBC-150 repeats from D. martensis further splits into three main branches corresponding to the three main variants of DBC-150 found in this species.…”
Section: A2-f/r B1-f/r Dbc-f/r A2-f/r B1-f/r Dbc-f/r Markermentioning
confidence: 94%